A study on the professional identity intervention of Chinese new nurses by Balint groups from the perspective of ABC theory of emotion-hong - Qiong Liu; Lidan Su; Xinxin Pan; Xiaofeng Jin (BMC Nursing)
Abstract Objective To explore the intervention effect of ABC theory on the professional identity and irrational beliefs of new Chinese nurses in Balint groups (BGs). Methods A total of 110 Chinese nurses newly recruited in August 2021 by a grade-A tertiary general hospital in Wenzhou, Zhejiang province were adopted as research objects. They were randomly divided into an experimental group and a control group, the experimental group spread out in groups to practice the BGs, and the control group did not have any intervention. Before and after the intervention, the Chinese nurses were assessed with a general information questionnaire, nurses’ professional identity rating scale, and irrational beliefs rating scale. Results After the intervention, the scores of Chinese nurses’ professional identity in the experimental group and the control group were 115.51 ± 14.03 and 106.58 ± 14.45 respectively, belonging to the middle level, and the scores of Chinese nurses’ irrational beliefs in the two groups were 49.33 ± 12.30 and 59.98 ± 13.10 respectively, and the differences were both statistically significant (p < 0.05). Conclusion Introducing the ABC theory of emotion into BG can reduce irrational beliefs and enhance the professional identity of Chinese new nurses.